Formation of a liquid crystalline phase from phosphatidylcholine at the oil-aqueous interface - Benjamins, Jan-Willem (Langmuir : the ACS journal of surfaces and colloids, 2005)
Adsorption of phospholipid (1,2-dioleoyl-sn-glycero-3-phosphatidylcholine) and formation of a surface phase at the oil-water interface has been followed by using ellipsometry. The properties of the interfacial phase were found to depend strongly on whether phospholipid was added to the oil phase or to the aqueous phase as liposomal structures. In the latter case a monolayer formed, while if the phospholipid was supplied from the oil phase a lamellar phase appeared at the interface. The effect on the stabilizing surface phase of a surface-active protein (beta-lactoglobulin) was also investigated. The observations are important for understanding stabilizing properties of surface-active compounds commonly used to stabilize emulsions. In addition it has been demonstrated that ellipsometry can be used to study the initial process when a two-phase system consisting of a water and an oil phase is transformed into a three phase system or eventually to a one-phase system